2017
DOI: 10.1212/wnl.0000000000003653
|View full text |Cite
|
Sign up to set email alerts
|

Serum neurofilament is associated with progression of brain atrophy and disability in early MS

Abstract: Objective: To investigate a potential effect of riluzole on serum neurofilaments (Nf) compared to placebo and the relationship between longitudinal clinical and MRI outcomes and serum Nf levels.Methods: Serum samples were obtained from participants enrolled in a randomized double-blind trial of neuroprotection with riluzole vs placebo as an add-on to weekly interferon-b (IFN-b)-1a IM initiated 3 months after randomization. Nf measurements were performed by ELISA and electrochemiluminescence immunoassay.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
179
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 177 publications
(195 citation statements)
references
References 13 publications
7
179
4
Order By: Relevance
“…Short‐term studies have found that in patients with high baseline NfL, brain volume decreased more rapidly ( P = 0.05 at 12 months and P = 0.008 at 24 months) 15. Our BPF measurements of brain atrophy at 10 years consistently correlated with averaged yearly NfL levels, however, limited strength of association was gained by measurements beyond years 1–5.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Short‐term studies have found that in patients with high baseline NfL, brain volume decreased more rapidly ( P = 0.05 at 12 months and P = 0.008 at 24 months) 15. Our BPF measurements of brain atrophy at 10 years consistently correlated with averaged yearly NfL levels, however, limited strength of association was gained by measurements beyond years 1–5.…”
Section: Discussionmentioning
confidence: 50%
“…Shorter term studies have found correlations between new gadolinium‐enhancing lesions and serum NfL values 13, 15, 31. Patients with either brain, spinal, or both brain and spinal gadolinium‐enhancing lesions had higher serum NfL than those without 13.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might indicate that NfL is shed upon damage of long axons of the UMN. This is further supported by the rise of serum and CSF NfL in other diseases damaging the central nerve axons such as multiple sclerosis .…”
Section: Discussionmentioning
confidence: 73%
“…NfL crosses readily into the blood stream, and recent studies have demonstrated blood NfL to be a good estimate of NfL in the CSF. 14 NfL has been shown to be a good measure of treatment response in RRMS and also correlates with disability progressive in progressive MS. Ongoing studies will define normative values, biologic variability, and optimal testing methods.…”
Section: Phase 2 Trial Biomarkersmentioning
confidence: 99%